Evaluation Of Public Service Standart (Case Study At The Education And Training Agency Of Yogyakarta Special Region) - Muhammad Khozin; Gerry Katon Mahendra; Anike Febriyani Nugraha (Universitas Muhammadiyah Ponorogo, 2020)
Improvement and quality assurance of public services is very needed, therefore the Government through Law Number 25 of 2009 concerning Public Services and Minister of Administrative Reform and Bureaucratic Reform Number 15 of 2014 concerning Guidelines for Service Standards requires that every public service provider be obliged to establish and apply Public Service Standards for each type of service that it provides. One of them is the Yogyakarta Education and Training Agency as a public service provider in the form of education, training, and competency development for the State Civil Apparatus. Public service standard documents that have been prepared by the Yogyakarta Education and Training Agency in 2017 need to be evaluated because they allegedly did not meet the method in the preparation process. The research conducted is a literature review with data mining techniques using observation techniques, interviews, mini focus group discussions and public hearings. Based on the research results it is known that the public service standard documents that have been owned by the Yogyakarta Education and Training Agency are still not comprehensive, but this solution is then obtained after an analysis and discussion with stakeholders at the Yogyakarta Education and Training Agency has also successfully identified various types of services that need to be it is prioritized to develop public service standards.